Cultural Analytics and the Politics of Representation: Mapping the Jewish Presence in Egypt’s al-Risālah (1933–1953) - Eid Mohamed (18147589) (2025)
This article investigates the representation of Jews in al-Risālah, a major Egyptian literary magazine (1933–53), by integrating Cultural Analytics and postcolonial theory. Using digital text analysis methods, it identifies and interprets patterns of Jewish representation within al-Risālah’s archive, uncovering how Arab intellectuals negotiated Jewishness amid the political tensions of the interwar and early postwar periods. This interdisciplinary approach enables a nuanced examination of cultural production, bridging quantitative modelling with close textual reading to reveal the ambivalences of Arab print discourse during a pivotal historical moment. The study’s significance lies in its digital examination of media texts published during the rise of Zionism and the establishment of Israel, an era that reshaped intercommunal relations across the Arab world. As Arab Jews began departing Egypt en masse, al-Risālah’s evolving depictions of Jews became symptomatic of broader anxieties over national identity, religious difference, and colonial legacies. Structured in two parts, the first contextualizes al-Risālah within anti-colonial and post-Ottoman intellectual currents, illustrating how the magazine became a platform for competing visions of Arab modernity. The second part synthesizes distant reading with interpretive analysis to assess how al-Risālah conceptualized Jews: as symbols of modernity, victims of Western imperialism, or threats to Arab sovereignty. These portrayals are not merely historical curiosities but inform contemporary understandings of ethno-religious identity and political belonging. By fusing digital humanities tools with a postcolonial critique of knowledge production, this study contributes a new methodological and epistemological model for analysing Arab print culture, representation, and media history. Other Information Published in: Digital Scholarship in the Humanities License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/llc/fqaf114